Mengembangkan Kreativitas Anak Melalui Permainan Puzzel Di KB AL Ikhlas Wonosobo - Dina Septiya Zahra; Nirmaya Triyanti; Shofiya Rohmatun Azizah; Vava Imam Agus Faisal (Intellektika : Jurnal Ilmiah Mahasiswa, 2026)
This article provides an in-depth examination of the role of puzzle games as an educational tool for fostering creativity in early childhood. Creativity is defined as the ability to generate new, meaningful, and useful ideas or solutions that contribute to a child's overall development. In the context of early childhood education, creativity is a crucial developmental component, influencing cognitive, emotional, social, and problem-solving abilities that support future learning. Using a descriptive qualitative method, this study illustrates how children interact with puzzle activities and how these interactions stimulate their creative thinking skills. Data were collected through observations, interviews with teachers, and documentation of children’s activities while engaging with puzzle games. The findings reveal that puzzle activities significantly stimulate multiple aspects of children’s development. Cognitively, puzzles enhance visual – spatial skills, pattern recognition, visual memory, as well as logical and analytical thinking. Motorically, handling and arranging puzzle pieces helps strengthen fine motor skills and hand – eye coordination. From a socio – emotional perspective, puzzles teach children cooperation, turn-taking, perseverance, and resilience when facing challenges. Completing puzzles also fosters a sense of accomplishment and boosts self-confidence. Furthermore, puzzle play encourages children to experiment, develop strategies, and express imagination through exploring shapes and structures. Overall, the study concludes that puzzles serve as a highly stimulating educational medium capable of effectively fostering children’s creativity. The wide variation in puzzle types, shapes, and difficulty levels enables teachers to tailor activities according to individual developmental stages, including children with special needs. Thus, puzzles are not merely toys, but multifunctional educational tools that provide meaningful, engaging, and long-term benefits for early childhood learning.